Scenarios for change: Digital technologies and the future of food, land, and water systems - Arce Gomez, Daniela (2025)
This blog post presents a foresight workshop led by the Alliance of Bioversity International and CIAT and IWMI to explore how digital technologies could reshape food, land, and water systems in the Global South. Using design thinking and scenario building, the workshop developed people-centered narratives to inform inclusive, forward-looking strategies. The goal is to guide CGIAR and partners in making research and investment decisions that remain relevant across uncertain futures.